Early experience of atezolizumab plus bevacizumab treatment for unresectable hepatocellular carcinoma BCLC‐B stage patients classified as beyond up to seven criteria – Multicenter analysis. Issue 3 (2nd December 2021) - Hiraoka, Atsushi; Kumada, Takashi; Tada, Toshifumi; Hirooka, Masashi; Kariyama, Kazuya; Tani, Joji; Atsukawa, Masanori; Takaguchi, Koichi; Itobayashi, Ei; Fukunishi, Shinya; Tsuji, Kunihiko; Ishikawa, Toru; et al.
Abstract: Background/Aim: Although systemic therapy is recommended for patients with multiple intermediate stage unresectable hepatocellular carcinoma (u‐HCC) classified as beyond the up‐to‐7 criteria (UT‐7 out/multiple) as a transcatheter arterial chemoembolization (TACE) unsuitable condition, few reports have examined the therapeutic efficacy of atezolizumab plus bevacizumab combination therapy (Atez/Bev) in such cases. This study aimed to elucidate the therapeutic response of Atez/Bev in u‐HCC patients classified as UT‐7 out/multiple. Material/Methods: From September 2020 to September 2021, 95 u‐HCC Japanese patients classified as UT‐7 out/multiple/Child‐Pugh A were enrolled from 21 institutions (median age 76 years, males 73, Child‐Pugh 5:6 = 68:27, TNM stage II:III = 17:78). Therapeutic response was retrospectively evaluated using Response Evaluation Criteria in Solid Tumors (RECIST), ver. 1.1 and modified RECIST (mRECIST). Results: Atez/Bev was given as first‐line treatment to 52 (54.7%). Objective response rate (ORR)/disease control rate (DCR) at six weeks of RECIST and mRECIST were 17.7%/84.7% and 42.5%/86.2%, respectively. Median PFS was 8.0 months (median observation period: 6.0 months). Child‐Pugh A/modified Albumin‐bilirubin grade (mALBI) 1 and 2a at baseline, 3, 6, and 9 weeks, were 100%/69.4%, 89.8%/57.3%, 94.8%/65.3%, and 91.4%/60.0%, respectively. Among adverse events (any‐grade, >10%) during the present observation period, general fatigue was most frequent (23.2%), followed by urine protein (21.1%), appetite loss (20.0%), and hypertension (13.7%). Conclusion: Atez/Bev treatment showed favorable therapeutic response with less influence on hepatic function, suggesting it as a useful therapeutic option for patients with such condition.